Tang Junyi Confucian Philosophy and the Challenge of Modernity - Fröhlich, Thomas (Modern Chinese Philosophy, 2017)
Both inside and outside of China, there have been heated debates about Confucian democracy, Confucian values and ethics, and Confucian alternatives to Western models of modernization. In many respects, however, the discussions have reached an impasse: Whereas some observers tend to depict Confucianism as a panacea for all kinds of political and social ills in East Asian and Western societies, others consider it to be a mere vestige of the Chinese tradition which lacks any relevance for contemporary discourse. The present study proposes a way through this impasse based on a critical examination of the modern Confucian project developed by the exiled philosopher Tang Junyi (1909-1978). Tang's comprehensive reinterpretation of Confucianism ranks among the most ambitious philosophical projects in modern Chinese history.